Dithienobenzoxadiazole-based wide bandgap donor polymers with strong aggregation properties for the preparation of efficient as-cast non-fullerene polymer solar cells processed using a non-halogenated solvent. Issue 1 (7th December 2020) - Jiang, Haiying; Qin, Guoming; Zhang, Lianjie; Pan, Feilong; Wu, Zhuhao; Wang, Qian; Wen, Guanzhao; Zhang, Wei; Cao, Yong; Chen, Junwu
Abstract : The efficient as-cast polymer solar cells processed by non-halogenated solvent are achieved through new dithienobenzoxadiazole-based wide bandgap donor polymers with strong aggregation property. Abstract : The efficient as-cast polymer solar cells processed using a non-halogenated solvent are suitable for roll-to-roll printing. In this study, three dithienobenzoxadiazole-based wide bandgap polymers PBOffDT, PBOTT and PBOTVT, which have different backbone structures, were designed and synthesized to reveal the relationship between the backbone structure and photovoltaic performance. The backbone structure had a great influence on the energy level, absorption behavior, aggregation and packing behavior of the polymers. PBOffDT exhibited the deepest HOMO level, the strongest aggregation and the most ordered crystallinity among the three polymers. IT-4Cl was used as the acceptor to fabricate PSC devices, and power conversion efficiencies (PCEs) of 10.56, 8.25 and 3.12% were obtained for PBOffDT, PBOTT and PBOTVT based as-cast devices using non-halogenated 1, 3, 5-trimethylbenzene (1, 3, 5-TMB) as the solvent, respectively. PBOffDT:IT-4Cl based devices showed the highest open circuit voltage ( V oc ), which can be ascribed to the deepest HOMO level of PBOffDT. Meanwhile, as revealed by the surface energy measurement, PBOffDT had suitable compatibility with IT-4Cl, and thus a favorable morphology can be achieved leading to efficient exciton dissociation, suppressed recombination and balanced charge transport for the PBOffDT:IT-4Cl devices. Our studies showed that the enhancement and retention of polymer crystallinity can be valuable to enhance the photovoltaic performance of the DTfBO-based polymer in non-halogenated solvent processed as-cast devices.